TEACHING HISTORY THROUGH THE EYES OF ETHNIC-RACIAL DIVERSITY: READINGS OF THE CONTINUOUS TRINING OF TEACHERS - Jean Mac Cole Tavares Santos; Patrícia Cristina de Aragão Araújo (Editora da Universidade de Santa Cruz do Sul, 2013)
This text examines the theme african-Brazilian school from reflections on the continuing education and the teaching of history. Our goal is therefore to investigate the importance of including the teaching of this subject in the discussions around the african-Brazilian culture from the ethnic-cultural diversity that exists in school. This is a research and development here present the first impressions of study, support us in the theoretical framework of the work of Certeau, Cavallero, Lino Gomes, and Freire Cunha Júnior. As a methodological approach, we seek in ethnomethodology from the sign paradigm in the light of Coulon and Guinzburg, people and traces the evidence that the texts in the present. Preliminary results indicate that the discussion of diversity and dimensionality in the context of school, especially in the field of teaching of history, can be extended from the participation of educational and action / the teacher and thus contributing to the dialogue among differences and minimization of exclusion and greater articulation of knowledge of black culture.